2017
DOI: 10.3390/app7030306
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Hard Segments on the Thermal, Phase-Separated Morphology, Mechanical, and Biological Properties of Polycarbonate Urethanes

Abstract: Abstract:In this study, we have fabricated a series of polycarbonate polyurethanes using a two-step bulk reaction by the melting pre-polymer solution-casting method in order to synthesize biomedical polyurethane elastomers with good mechanical behavior and biostability. The polyurethanes were prepared using dibutyltin dilaurate as the catalyst, poly(1,6-hexanediol)carbonate microdiols (PCDL) as the soft segment, and the chain extender 1,4-butanediol (BDO) and aliphatic 1,6-hexamethylene diisocyanate (HDI) as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…The presence of two independent clearly segregated relaxation peaks with different widths and degrees of irregularity in each loss tangent curve in the temperature range of about 250-450 K indicates an inhomogeneous, partially incompatible, and partly immiscible polymeric system with a three-phase-separated morphology [28], which consists of a hard melamine resin phase, a hard phenol-formaldehyde resin phase, and a soft nitrile rubber phase. Generally, the broadening of the DMA damping peaks corresponding to the glass transition events is the indication of the compatibilisation of the multi-component polymeric systems associated with molecular mixing and chemical interactions of its individual components.…”
Section: Dynamic Mechanical Analysismentioning
confidence: 99%
“…The presence of two independent clearly segregated relaxation peaks with different widths and degrees of irregularity in each loss tangent curve in the temperature range of about 250-450 K indicates an inhomogeneous, partially incompatible, and partly immiscible polymeric system with a three-phase-separated morphology [28], which consists of a hard melamine resin phase, a hard phenol-formaldehyde resin phase, and a soft nitrile rubber phase. Generally, the broadening of the DMA damping peaks corresponding to the glass transition events is the indication of the compatibilisation of the multi-component polymeric systems associated with molecular mixing and chemical interactions of its individual components.…”
Section: Dynamic Mechanical Analysismentioning
confidence: 99%
“…The tensile strain at break of SMPU is inversely proportional to the Young's modulus [55]. The chain flexibility of the prepared polyurethanes is provided by the presence of PCL4000 fragments in SS.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…72 Zhu et al reported that relative to other types of TPU, TPU synthesized using PCDL as the soft chain end demonstrated more favorable flexibility and elongation at break, as well as biocompatibility properties. 73 Ehrmann et al applied TPUs synthesized using PCDL to develop biodegradable materials in soft tissue engineering. 74 The present study was focused on creating a TPU material suitable for use under room temperature.…”
Section: Introductionmentioning
confidence: 99%